First steps to setting up the Hungarian spatal planning support system for the implementation of the green infrastructure network concept - Vaszócsik, Vilja; Göncz, Annamária; Schneller, Krisztián; Tóth, Péter; Prokai, Réka (JOURNAL OF LANDSCAPE ECOLOGY, 2014)
Summary: In 2009, the European Commission has adopted the concept of green infrastructure. Based on this new approach the biodiversity preservation systems and the assessments of ecosystem services will be developed in a widely accepted policy and implementation framework. Spatial planning plays a crucial role in the implementation of this new concept. The Green Infrastructure project started in 2012, where the Regional Environmental Center (REC) coordinated the exchange of experiences and good practice transfer in Hungary. The REC involved the Lechner Lajos Knowledge Center to support this latter activity and undertaken the role of developing a spatial planning tool. The testing areas were the Szob and Veresegyház micro regions. As part of the decision making system useful and informative indicators were defined on natural value assessment, forestry / agricultural suitability and complex spatial development potentials (LLTK, 2014). The system was developed based on the territorial planning system of Barcelona (SITxell), which operates on a very similar principle.
Keywords: green infrastructure; spatial planning; decision support system; natural value; land use